IoT-Enabled Medication Reminder System with Alarm Delay Function - Mardhiyyah, Rodhiyah; Nuryadi, Satyo; Zulkhairi; Ali Habibie, Raihan Ghifari; Machfud, Achmad Agim (Fidelity : Jurnal Teknik Elektro, 2024)
Medication compliance is essential to support the recovery of one's health. Prescribed medication for patients should be taken in accordance with the instructions, such as taking it after a meal, so patients should adhere to these guidelines for the medication to work optimally. Typically, medication reminder devices that have been designed continuously sound alarms until the user takes the medication. This allows users to meet the requirements before taking the medication, for example, having a meal if necessary. This medication reminder device is built with a snooze button that allows users to postpone the alarm so they can complete the necessary tasks before taking the medication. It also features LED lights to indicate the medication box that needs to be taken. The LCD displays real-time information, the next medication time, and the type of medication to be taken. The result of creating this device is that it can activate alarms according to the specified schedule and activate the LED lights corresponding to the medication box to be taken. The snooze function works when the snooze button is pressed and when the medication is not taken for 1 minute. After being postponed, the alarm will reactivate after 3 minutes. Additionally, notifications are also successfully sent to the Telegram application connected to the device. There is a delay of approximately 15-30 seconds when activating the alarm. Messages are sent to Telegram at three (3) times.